Degree of Educational Portal Use in the Schools of the Future from its Teachers’ Perspective - Daradkah, Hamzah Mahmoud (International Journal of Educational Technology and Learning, 2020)
The aim of this paper is to reveal the degree of educational portal use in His Majesty King Hamad’s project for schools of the future from its teachers’ perspective in the light of gender variable, qualification variable, variable of experience in teaching, and training courses variable. To achieve the above-mentioned purpose, a questionnaire was designed meticulously and was validated before use. The research sample was composed of 340 teachers, randomly selected from the teachers of His Majesty King Hamad’s Project for Future Schools in the Kingdom of Bahrain. The results of the study showed a high degree of the educational portal use in His Majesty King Hamad’s project for schools of the future from its teachers’ perspective. The results indicated that there are no statistically significant differences at the significance level of (α ≤ 0.05) between the sample estimates for the degree of educational portal use as a system for e-learning management in future schools attributed to the variables of gender and experience in teaching, while there are statistically significant differences attributable to qualification variable, training courses and the interaction between them. The study recommended the necessity of holding more courses and training workshops on how to employ the educational portal in various educational and administrative aspects, the necessity of providing teacher’s Guides that explain how to use the educational portal in the educational process.